Molecular biology of spirochetes - Cabello, Felipe C (IOS Press, 2013)
Diseases produced by spirochetes, including Lyme borreliosis, syphilis and leptospirosis, are on the rise worldwide. This volume focuses on a series of state-of-the-art presentations of the research taking place in the laboratories of the contributors, and serves as an introduction to those individuals entering in the field of spirochete research.